T–M coupled effects on cracking behaviors and reliability analysis of double-notched crustal rocks. (June 2016) - Zuo, Jian-Ping; Wang, Xi-Shu; Mao, De-Qiang; Wang, Chun-Lai; Jiang, Guang-hui
Highlights: The thermo-induced crack density is direct proportion to elevated temperatures. The thermo-mechanical-induced cracks occurred mainly in harder and larger quartz grains. The threshold value of thermo-induced crack density is about 50–60 mm −2 . Weibull analysis is good suit for thermo-mechanical-induced fracture strength. The failure probability (%) of crustal rock can be estimated by Weibull model. Abstract: Experiments on crack initiation and propagation of double-notched rocks caused by thermal–mechanical loading were carried out by using in-situ SEM observation technique. The results indicated that thermal-induced or thermal–mechanical-induced cracking mechanisms depend strongly on thermal deformation mismatch between the mineral compositions. Micro cracks initiation occurred mainly in the harder and larger quartz grains, but the failure strength of rock did not adequately degrade when surface micro crack density is less than 40 (mm −2 ). At last, a reliability analysis of 3-parameter Weibull distribution model is presented to discuss the effect of the thermal-induced micro crack on failure strength of rock. Threshold value by thermal-induced micro crack density to influence on the failure strength of crustal rock can be estimated at about 50–60 (mm −2 ).